STATE OF SYSTEMIC AND LOCAL IMMUNE RESPONSE IN PATIENTS WITH OSTEOARTICULAR TUBERCULOSIS IN THE PERIOPERATIVE PERIOD (World Bulletin of Public Health, 2026)
Bone and joint tuberculosis represents one of the most severe extrapulmonary forms of tuberculosis infection, constituting, according to various data, from 3 to 5% in the structure of all registered cases of tuberculosis. The disease is characterized by steadily progressive destructive damage to bone tissue, which often leads to persistent loss of joint function, disability of patients, and a significant decrease in their quality of life.
Keywords: Osteoarticular tuberculosis; bone and joint tuberculosis; systemic immune response